The Extent of Implementing the Strategy of Solid Waste Management in Baquba City - Poll search - محمد علي عالية جواد; عمران شكرية عبود (Journal of Economics and Administrative Sciences, 2020)
The research aims to identify the reality of the management strategy followed in the treatment of solid waste in the city of Baquba, and what strategies are used to treat solid waste, and the extent of the application of these strategies, through personal interviews with leading cadres in the Directorate of Baquba Municipality, their assistants and heads of departments, they numbered (55) Individuals. The descriptive method was adopted through a questionnaire prepared to measure the extent of the implementation of the strategy of solid waste management in the city of Baquba and using statistical tools including (arithmetic mean, standard deviation, relative importance, the gap). The research reached a number of conclusions, the most important of which is the failure of the Baquba Municipality to implement any strategy of solid waste treatment strategies. Based on the findings of the research, a set of recommendations that can be relied upon and benefited in improving the environmental situation in the city of Baquba, the most important of which is to seek to increase the experience and efficiency of employees working in the field of solid waste, and the need to implement a recycling strategy for materials in Solid waste, as it is a clean and easy process and provides a good financial return to the municipality with the need to educate citizens of the importance of cooperation with the municipality in the implementation of the strategy of solid waste treatment and preservation of the environment and make the city of Baquba clean and beautiful and healthy environment.